The Incidence of Depression in Elderly Patients with Hypertension Stage 2 in Karang Taliwang - Tantowi, Natalia; Wedayani, Anak Agung Ayu Niti; Pujiarohman, Pujiarohman; Adni, Azizatul; Kusuma, I Gusti Ketut Artha Jaya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Depression is a common mental health disorder in the elderly, often coexisting with chronic conditions like hypertension. This study examines the relationship between depression and hypertension stage 2 among elderly individuals at Puskesmas Karang Taliwang, considering age and gender. A cross-sectional study of 30 elderly patients used a validated questionnaire to assess depressive symptoms. Results showed a significant association between age (≥60 years) and depression, while gender had no statistical correlation. Hypertension stage 2 was also significantly linked to depression, though with a small effect size. These findings highlight the need for integrated healthcare strategies addressing both mental and cardiovascular health in the elderly. Further research is needed to explore underlying mechanisms and potential interventions.